DEVELOPMENT OF PROBOLINGGO TRADITIONAL CULTURE ETHNOMATHEMATICS OF COMICS IN FLAT BUILDING GEOMETRY MATERIALS FOR STUDENTS - Putri, Anisa Yulia; Arisanti, Kustiana (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The ability of students in learning geometry needs to be maximized in order to encourage increased logical thinking skills. Teachers in learning geometry are expected to use media that attract the attention of their students. One of the media that is expected to arouse students' learning motivation is comics. So this research will develop a prototype of comic media based on traditional cultural ethnomathematics in learning geometry. For this reason, the research and development (R&D) method was used with Plomp development as a research framework. Prototype I Comics were assessed by two validators and an art teacher who analyzed their readability. Based on the steps of the development method: the initial investigation, design, construction, and testing, evaluation and revision steps, a comic prototype of rectangular and triangular material with traditional cultural ethnomathematics nuances is obtained which meets validity and readability. The comics developed have not been implemented for MTs students in the school environment